The Application of Project-Based Learning to Enhance Student’s Proficiency in Producing Written Reports - Shalzsabilla Hakim; Syafrizal Syafrizal (Publikasi Indonesia, 2024)
This study was quantitative. The purpose of this project was to demonstrate how PjBL could help students overcome obstacles and improve their report-writing abilities for the XI grade of SMAN 2 Rangkasbitung. Twenty-five learners were the study’s subject. The research study used tests and observation procedures as its instruments. The research was done in three following steps: pre-test, treatment, and post-test. Based on the result of the post-test, students writing report text ability showed an improvement. It was proven by the pre-test mean; the result of the mean was 67.00 while the student’s post-test mean was 78.00. To conclude, the student’s writing ability of the eleventh grade SMA N 2 Rangkasbitung presents a contrast difference before and after the treatment. Overall. It’s because most of the students are not familiar enough with the general structure of report text, hence they are unable to write a good report text. To recommend, the teacher can use PjBL as one of another approaches.